2022
DOI: 10.1111/clr.13933
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge preservation with guided bone regeneration or socket seal technique. A randomised, single‐blind controlled clinical trial

Abstract: Objectives: To compare radiographic bone changes, following alveolar ridge preservation (ARP) using Guided Bone Regeneration (GBR), a Socket Seal (SS) technique or unassisted socket healing (Control). Material and methods:Patients requiring a single rooted tooth extraction in the anterior maxilla, were randomly allocated into: GBR, SS and Control groups (n= 14/). Cone Beam Computed Tomography (CBCT) images were recorded post-extraction and at 4 months, the mid-buccal and mid-palatal alveolar ridge heights (BAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 69 publications
1
41
1
Order By: Relevance
“…In this study, the modest level of participants' perception of pain, swelling, bleeding, bruising, and root sensitivity during the first week following ARP was within the range of well toleration. The VAS scores for these perceptions, however, did not concur with those reported in other studies following other ARP treatment modalities (Barone et al, 2013;Festa et al, 2013;Macbeth et al, 2022), particularly in terms of pain, bleeding, and bruising scores during the first 2 days of healing. In fact, the combined use of DBBM and EMD in our study has significantly increased the VAS scores for bruising on Day 1, bleeding and bruising on Day 2, and even swelling on Day 6.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study, the modest level of participants' perception of pain, swelling, bleeding, bruising, and root sensitivity during the first week following ARP was within the range of well toleration. The VAS scores for these perceptions, however, did not concur with those reported in other studies following other ARP treatment modalities (Barone et al, 2013;Festa et al, 2013;Macbeth et al, 2022), particularly in terms of pain, bleeding, and bruising scores during the first 2 days of healing. In fact, the combined use of DBBM and EMD in our study has significantly increased the VAS scores for bruising on Day 1, bleeding and bruising on Day 2, and even swelling on Day 6.…”
Section: Discussioncontrasting
confidence: 78%
“…The strength of this paper is the routine use of autologous particulate bone harvested with a simple drill from the mandibular ramus ( Figure 2 ) and the use of CBCT referral for each measurement reported. Although many papers have reported the possible benefits of socket preservation after tooth extraction, few papers have used standardized preoperative and postoperative CBCT images to evaluate the measurements [ 34 ]. The majority of socket preservation research has compared preoperative measurements performed on intraoral bidimensional radiography with postoperative bidimensional or three-dimensional images, or on a resin template with periodontal probe measurements and clinical measurements of the bone width [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MacBeth et al, in their randomized, single-blind controlled clinical trial, used CBCT immediately after tooth removal and four months after extraction. This methodology was revealed to be more accurate as the absence of a tooth in the images allowed for more detailed measurements [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial comparing guided bone regeneration (GBR) versus socket seal technique revealed that GBR was more effective at reducing radiographic bone resorption. 34 To date, mainly bone of deproteinized bovine origin or alloplastic materials was used as graft material. 35 These materials showed the features of space maintaining and were embedded in the bone matrix in formation.…”
Section: Discussionmentioning
confidence: 99%